2021
DOI: 10.1097/rhu.0000000000001795
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Rheumatologists in Latin America

Abstract: Background: Rheumatology is considered a low-risk specialty, but studies have shown a prevalence of burnout between 42% and 51%. Objectives:The aim was to determine the prevalence of burnout in rheumatologists in Latin America and the factors associated with it.Methods: Cross-sectional study based on a survey completed through Google Forms platform that was sent by the national rheumatology associations of Latin America. Burnout was assessed with the Maslach Burnout Inventory. Data were analyzed using the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…It showed that, at the time of our survey, approximately 68% of the rheumatologists studied had at least 1 burnout symptom, 3.9% had exhaustion, 19.6% had cynicism, and 54.9% had low professional efficacy. These findings support recent reports that more than 50% of rheumatologists are experiencing burnout 1,3 . The results of a multivariate regression analysis suggested that higher grit was significantly associated with higher professional efficacy.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It showed that, at the time of our survey, approximately 68% of the rheumatologists studied had at least 1 burnout symptom, 3.9% had exhaustion, 19.6% had cynicism, and 54.9% had low professional efficacy. These findings support recent reports that more than 50% of rheumatologists are experiencing burnout 1,3 . The results of a multivariate regression analysis suggested that higher grit was significantly associated with higher professional efficacy.…”
Section: Discussionsupporting
confidence: 89%
“…22 Academic rheumatologists' treatment of intractable chronic diseases requires engagement in long-term physician-patient relationships, and, in conjunction with this, they also experience pressure to perform successful research (a key requisite for tenure) and have uncertainty regarding their career progression. [2][3][4] This underlines the importance of professional efficacy for such professionals. Although the impact of grit on burnout should be carefully considered, as the concept of grit becomes more keenly defined, it is possible that academic rheumatologists with higher grit are better able to attribute positive meaning to difficult tasks and, as a result, complete tasks they start and maintain professional efficacy.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations